2013
DOI: 10.1007/s11427-013-4523-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanism of impact resistance in the woodpecker’s head and its application

Abstract: The woodpecker does not suffer head/eye impact injuries while drumming on a tree trunk with high acceleration (more than 1000×g) and high frequency. The mechanism that protects the woodpecker's head has aroused the interest of ornithologists, biologists and scientists in the areas of mechanical engineering, material science and electronics engineering. This article reviews the literature on the biomechanisms and materials responsible for protecting the woodpecker from head impact injury and their applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…At the interface between the cartilagebone skeleton and the tissue layer, there is a hierarchical fiber connection [15]. The cranial bone of the woodpecker achieved a higher ultimate strength of 6.38 MPa compared with the Lark of 0.55 MPa [6,33,34], which suggested that the mechanical properties are sensitive to the shape of individual trabeculae [35]. Materials that contain more organic material are expected to exhibit greater flexibility under load [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…At the interface between the cartilagebone skeleton and the tissue layer, there is a hierarchical fiber connection [15]. The cranial bone of the woodpecker achieved a higher ultimate strength of 6.38 MPa compared with the Lark of 0.55 MPa [6,33,34], which suggested that the mechanical properties are sensitive to the shape of individual trabeculae [35]. Materials that contain more organic material are expected to exhibit greater flexibility under load [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Woodpeckers are commonly cited as the inspiration for the theorized protective effects of "tighter fit," based on their limited intracranial space (24,27). However, it seems scientifically implausible for slight increases in cranial fluid volume to functionally mimic woodpeckers' "unique anatomic structure," which includes numerous macroscopic (i.e., brain structure and orientation, skull thickness) and microscopic (i.e., various trabecular and biochemical qualities that influence mechanical properties) anatomic adaptations that collectively create impact-resistance (28). A jugular occlusion study in rats reporting decreased brain damage (24, 27) after a 900 g impact ( 15) has been used to justify its potential in sports (16,25).…”
Section: Inducing Tighter Fit Through Jugular Occlusion?mentioning
confidence: 99%
“…In this process, acceleration can reach 1000 times the acceleration of gravity, and velocity can reach six times the speed of sound [34]. However, the vibration caused by the strong impact does not damage or destroy the woodpecker's brain [35][36][37]. Therefore, it is one of the important development directions of current vibration control systems [38][39][40][41], which can simulate biological structures and functions in order to improve the performance of traditional vibration control devices.…”
Section: Introductionmentioning
confidence: 99%